A method for producing colorless moissanite with high efficiency and high productivity

By cutting and splicing small-sized seeds to form large-sized spliced ​​seeds, and physical vapor deposition is carried out on a flexible substrate, the problem of low preparation efficiency of colorless moissilite in the prior art is solved, and the problem of difficult to obtain large size is achieved. High efficiency and low cost colorless moissanite preparation.

CN118639319BActive Publication Date: 2025-02-25ZHEJIANG JINGYUE SEMICON CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411103407.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-02-25
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The prior art has low efficiency in preparing colorless moissanite and it is difficult to obtain large-sized colorless moissanite.

Method used

By cutting, aligning and splicing small-sized semi-insulating seeds, forming large-sized spliced ​​seeds, bonding them to the surface of the flexible substrate, and then physical vapor deposition is carried out to form colorless moissanite.

Benefits of technology

The preparation efficiency of colorless moissanite is improved, production costs are reduced, and the problems of cracking and poor partial area increase during the deposition process are effectively avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118639319B_ABST
    Figure CN118639319B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of moissanite production, and in particular to a method for manufacturing colorless moissanite with high efficiency and high production capacity, the method comprising the following steps: (S.1) cutting semi-insulating seed crystals to obtain seed crystals with regular shapes; (S.2) coating glue on the surface of the seed crystals with regular shapes and arranging and splicing them to obtain large-sized spliced ​​seed crystals; (S.3) bonding the large-sized spliced ​​seed crystals to the surface of a flexible substrate, and then coating glue on the other side of the flexible substrate; (S.4) bonding the flexible substrate together with the large-sized spliced ​​seed crystals in a physical vapor deposition device, and depositing silicon carbide crystals on the surface of the large-sized spliced ​​seed crystals by physical vapor deposition, thereby forming colorless moissanite. In the present application, small-sized seed crystals are cut and spliced ​​into large-sized spliced ​​seed crystals, and the seeds are bonded to the surface of a flexible substrate for deposition, thereby reducing the loss rate of moissanite while improving the preparation efficiency of colorless moissanite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of moissanite production, and in particular to a method for manufacturing colorless moissanite with high efficiency and high productivity. Background Art

[0002] There are several main methods for artificial synthesis of moissanite:

[0003] Physical vapor deposition method: This is the most commonly used method for artificially synthesizing moissanite. This method uses silicon carbide powder or carbon powder and silicon powder as raw materials, and through the process of physical vapor transmission under high temperature conditions, carbon atoms and silicon atoms are gradually deposited on the seed crystal, thus forming moissanite crystals.

[0004] Cold crucible method: First, heat the silicon carbide raw material to above 2000℃ under vacuum conditions to make it sublime into gas, and then cool the cold crucible to condense the gaseous silicon carbide into crystals on the crucible wall. The moissanite crystals synthesized by this method are larger, but the quality and purity may not be as good as those by the physical vapor transport method.

[0005] In addition to the above two methods, there are some other methods that can also be used to synthesize moissanite, such as chemical vapor deposition (CVD).

[0006] The authorization announcement number is CN109911899B, which discloses a method for preparing colorless moissanite, including: placing a high-purity semi-insulating silicon carbide wafer into a crucible, charging a furnace and setting growth parameters, heating the crucible, sublimating the high-purity semi-insulating wafer and recrystallizing it at the top of the crucible, cooling it out of the furnace to obtain colorless moissanite. The growth parameters are: temperature at 2000~2300℃, and pressure at 1~700 Torr. The method successfully solves the problems of raw material nitrogen content doping, moissanite gray-yellow color, and reuse of unqualified silicon carbide wafers. The utilization rate of unqualified silicon carbide wafers is improved, and colorless moissanite is obtained. However, no matter which method in the prior art is used, it is impossible to efficiently prepare large-sized colorless moissanite. Summary of the invention

[0007] The present invention aims to overcome the defects of the prior art that the preparation process of moissanite is low in efficiency and large-sized moissanite cannot be obtained, and provides a method for manufacturing colorless moissanite with high efficiency and high production capacity to overcome the above-mentioned shortcomings.

[0008] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0009] In a first aspect, the present invention first provides a method for producing colorless moissanite with high efficiency and high productivity, comprising the following steps:

[0010] (S.1) cutting the semi-insulating seed crystal to obtain a seed crystal with a regular shape;

[0011] (S.2) coating glue on the surface of seed crystals with regular shapes and arranging and splicing them to obtain large-sized spliced ​​seed crystals;

[0012] (S.3) bonding the large-sized splicing seed crystal to the surface of the flexible substrate, and then coating the other side of the flexible substrate with glue;

[0013] (S.4) The flexible substrate and the large-sized splicing seed crystal are bonded into a physical vapor deposition device, and silicon carbide crystals are deposited on the surface of the large-sized splicing seed crystal by physical vapor deposition, thereby forming colorless moissanite.

[0014] The existing method of preparing moissanite by physical vapor deposition is usually to directly bond the seed crystal to the top of the physical vapor deposition device (such as the crucible cover), and then start the heat source to heat the physical vapor deposition device, so that the silicon carbide is sublimated and vaporized and then deposited on the surface of the seed crystal, thereby obtaining a single crystalline colorless moissanite. However, the seed crystals currently used to deposit silicon carbide are usually small in size, resulting in low output and production efficiency of colorless moissanite. However, when the small-sized seed crystals are replaced with large-sized seed crystals, although the output and production efficiency are improved to a certain extent, the cost of the large-sized seed crystals is higher than that of the small-sized seed crystals. Therefore, based on the above reasons, the existing production of colorless moissanite is still limited by problems such as low production efficiency and high production cost.

[0015] The first key point in the manufacturing process of the colorless moissanite in the present application is that it first obtains a large-sized spliced ​​seed crystal by cutting, arranging and splicing small-sized semi-insulating seed crystals in sequence. After the large-sized spliced ​​seed crystal is placed in a physical vapor deposition device, it can greatly improve the efficiency of preparing colorless moissanite by the physical vapor deposition method.

[0016] It should be noted here that in order to reduce the manufacturing cost of colorless moissanite, the semi-insulating seed crystals used in step (S.1) of the present application can be selected from seed crystals with poor edges eliminated in the semiconductor industry. By cutting off the parts with poor edges, they can be normally used in the preparation process of colorless moissanite in the decoration industry.

[0017] In addition, it should be noted that after the application splices the small-sized seeds after cutting into large-sized spliced ​​seeds, there will be certain gaps between the small-sized seeds, so the structure of this part of the gap will change in the subsequent colorless moissanite deposition process. Unlike the traditional silicon carbide used in the semiconductor field, the purpose of this application is to form moissanite for the decoration field, so it does not have very high requirements for the crystal integrity of the whole silicon carbide crystal formed, and it needs to be cut and polished in the subsequent processing process to form the final moissanite product, so there will inevitably be more losses in this process. Therefore, the colorless moissanite prepared in this application only needs to cut and remove this part of the splicing in the subsequent processing process to be used for the production of moissanite products, and will not increase the loss rate of moissanite too much.

[0018] The seed crystal used in the traditional silicon carbide deposition process is usually a complete piece, so its physical and chemical properties are isotropic, so the adverse effects caused by the seed crystal itself can be ignored during the physical vapor deposition process. In the present application, since the large-sized spliced ​​seed crystal itself is obtained by cutting and splicing several different seed crystals, there are certain differences in performance between different small seed crystals. Therefore, if the large-sized spliced ​​seed crystal is directly bonded to a rigid physical vapor deposition device (such as a crucible cover), due to the different thermal expansion and contraction coefficients between different small-sized seed crystals and between the seed crystal and the physical vapor deposition device, there will be a large stress between the seed crystals and between the seed crystal and the physical vapor deposition device, which will cause the area of ​​the defective part of the seam between the small-sized seed crystals to increase significantly, and even cause the final moissanite product to crack and other problems, thereby greatly reducing the loss rate of moissanite.

[0019] Therefore, the second key point of the colorless moissanite in the present application in the manufacturing process is that after the small-sized seed crystals are spliced ​​into large-sized spliced ​​seed crystals, the large-sized spliced ​​seed crystals are first bonded to the surface of a flexible substrate, and then the flexible substrate with the large-sized spliced ​​seed crystals is bonded to the inside of a physical vapor deposition device for physical vapor deposition. Therefore, the flexible substrate can effectively buffer the thermal expansion and contraction between the seed crystals and between the seed crystals and the physical vapor deposition device, thereby effectively eliminating stress, thereby effectively avoiding cracking and the defects of increased area of ​​defective parts during the deposition process of the moissanite.

[0020] In summary, the present application effectively improves the preparation efficiency of colorless moissanite by cutting and splicing small-sized seed crystals. At the same time, the present application effectively reduces the stress between the seed crystals and between the seed crystals and the physical vapor deposition device by bonding the large-sized spliced ​​seed crystals to the surface of the flexible substrate during the preparation of the moissanite, thereby effectively avoiding the problem of cracking and increase in the area of ​​defective parts of the colorless moissanite.

[0021] Preferably, the step (S.1) is a high-purity semi-insulating silicon carbide wafer with poor edge quality.

[0022] Preferably, the seed crystal thickness in the step (S.1) is 300-500 μm;

[0023] The diameter of the large-sized spliced ​​seed crystal in the step (S.2) is 300-800 mm.

[0024] Preferably, the glue in step (S.2) and step (S.3) is any one of photoresist, paraffin, polyamide, and white sugar solution.

[0025] Preferably, the glue coating method in step (S.2) and step (S.3) is spin coating with a glue spreader;

[0026] The glue has a viscosity of 1000-1500cp;

[0027] The speed of the glue leveling machine is 10000 revolutions / s, and the thickness of the glue film of the glue leveling machine is 1-100 μm.

[0028] Preferably, the bonding process of the large-sized spliced ​​seed crystal and the flexible substrate in the step (S.3) includes: applying a pressure of 1-15T under vacuum and a temperature of 500-1200°C.

[0029] The bonding process in this application is carried out at a temperature of 500-1200°C, under which the molecules of the glue can be made more active, enhancing its fluidity and wettability, thereby better filling the tiny gap between the seed crystal and the flexible substrate and improving the tightness of the bonding; the pressure helps to make the seed crystal and the substrate more closely bonded, further enhancing the bonding strength. At the same time, the vacuum environment can effectively reduce the generation of bubbles and prevent bubbles from forming gaps at the bonding interface, thereby improving the quality and stability of the bonding.

[0030] Preferably, the flexible substrate is a combination of one or more of graphite paper, polyimide film, polysiloxane film and ultra-thin glass.

[0031] Preferably, the surface roughness of the flexible substrate is 0.1-2 μm, and the thickness is 0.1-1 mm.

[0032] By keeping the roughness within the range of 0.1-2μm, this application can provide a certain microscopic roughness to increase the mechanical interlocking effect between the seed crystal and the substrate, enhance the adhesion of the seed crystal, and not be too rough to cause uneven seed arrangement or gaps. At the same time, moderate surface roughness helps to evenly distribute the glue and provide uniform initial conditions for crystal growth, thereby ensuring the uniformity of thickness and quality of the subsequently deposited silicon carbide crystals.

[0033] The thickness of 0.1 - 1mm can provide sufficient strength for the substrate, making it not easy to deform or break during the production process, especially when subjected to pressure and temperature changes. In addition, the appropriate thickness helps to achieve good heat transfer and thermal balance during crystal growth. It will not cause heat accumulation due to excessive thickness, affecting the quality of crystal growth, nor will it be too thin to effectively buffer temperature changes.

[0034] Preferably, the physical vapor deposition device comprises a hollow graphite container, the interior of the graphite container is filled with high-purity silicon carbide powder, and the flexible substrate is bonded to the top of the graphite container.

[0035] Preferably, the physical vapor deposition method comprises the following steps:

[0036] (1) heating and evacuating the physical vapor deposition device to remove impurity gases in the physical vapor deposition device;

[0037] (2) introducing argon gas into the physical vapor deposition device for thermal field protection, and adjusting the gas pressure inside the physical vapor deposition device to 1-50 mbar;

[0038] (3) The temperature inside the physical vapor deposition device is controlled at 2000-2400°C, and the physical vapor deposition time is 100-500 hours.

[0039] Therefore, the present invention has the following beneficial effects:

[0040] (1) The present application effectively improves the preparation efficiency of colorless moissanite by cutting and splicing small-sized seed crystals;

[0041] (2) In the process of preparing moissanite, the present application bonds large-sized spliced ​​seed crystals to the surface of a flexible substrate, thereby effectively alleviating the stress between the seed crystals and between the seed crystals and the physical vapor deposition device, thereby effectively avoiding the problem of cracking of the colorless moissanite and the increase in the area of ​​defective parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 1 is a step diagram of a method for manufacturing colorless moissanite in an embodiment of the present invention.

[0043] Figure 2 This is a photo of the colorless moissanite prepared in Example 1 of the present invention.

[0044] Figure 3 This is a photograph of a colorless moissanite slice prepared in Example 1 of the present invention.

[0045] Figure 4 This is a step diagram of the method for manufacturing colorless moissanite in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0047] Example 1

[0048] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0049] (S.1) Cutting a semi-insulating seed crystal with bad edges by laser to form a seed crystal with a regular shape;

[0050] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0051] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 1 μm and a thickness of 0.1 mm, and a pressure of 10 T is applied under vacuum and a temperature of 800°C for 10 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0052] (S.4) The flexible substrate and the large-sized spliced ​​seed crystal are bonded to the top cover of the graphite crucible, and then the 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1500°C, and then vacuumed and protected with argon. This process is repeated 4 times to remove air impurities. The internal pressure of the graphite crucible is then controlled to 20mbar, and the graphite crucible is heated to 2200°C for physical vapor deposition. The process is stopped after 300 hours of continuous deposition, and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite. The actual photo of the prepared colorless moissanite single crystal ingot is shown in Figure 2. Figure 2 As shown, Figure 2 The colorless moissanite sliced ​​after slicing Figure 3 shown.

[0053] Example 2

[0054] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0055] (S.1) Cutting a semi-insulating seed crystal with bad edges by laser to form a seed crystal with a regular shape;

[0056] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1000 cp and a film thickness of 1 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0057] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 0.3 μm and a thickness of 0.1 mm, and a pressure of 1 T is applied under vacuum and a temperature of 1200°C for 20 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0058] (S.4) The flexible substrate and the large-sized spliced ​​seed crystal are bonded to the top cover of the graphite crucible, and then 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1000°C, and then vacuumed and protected with argon. This process is repeated 4 times to remove air impurities. The internal pressure of the graphite crucible is then controlled to 10mbar, and the graphite crucible is heated to 2100°C for physical vapor deposition. The process is stopped after 200 hours of continuous deposition, and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0059] Example 3

[0060] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0061] (S.1) As shown in the figure, a semi-insulating seed crystal with bad edges is cut by laser to form a seed crystal with a regular shape;

[0062] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1500 cp and a film thickness of 100 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0063] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 2 μm and a thickness of 0.2 mm, and a pressure of 5 T is applied under vacuum and a temperature of 800°C for 15 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0064] (S.4) The flexible substrate and the large-sized spliced ​​seed crystals are bonded to the top cover of the graphite crucible. Then, 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 2000°C and evacuated for 4 cycles. Argon gas is introduced to protect the thermal field. The internal pressure of the graphite crucible is controlled to 5 mbar. The graphite crucible is heated to 2400°C and the deposition is continued for 100 hours. The process is then stopped and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0065] Example 4

[0066] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0067] (S.1) As shown in the figure, a semi-insulating seed crystal with bad edges is cut by laser to form a seed crystal with a regular shape;

[0068] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0069] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 0.1 μm and a thickness of 0.1 mm, and a pressure of 15 T is applied under vacuum and a temperature of 500°C for 5 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0070] (S.4) The flexible substrate and the large-sized spliced ​​seed crystals are bonded to the top cover of the graphite crucible. Then, 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1800°C and evacuated for 4 cycles. Argon gas is introduced to protect the thermal field. The internal pressure of the graphite crucible is controlled to 1 mbar. The graphite crucible is heated to 2000°C and the deposition is continued for 500 hours. The process is then stopped and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0071] Example 5

[0072] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0073] (S.1) As shown in the figure, a semi-insulating seed crystal with bad edges is cut by laser to form a seed crystal with a regular shape;

[0074] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 300 mm;

[0075] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 0.1 μm and a thickness of 0.1 mm, and a pressure of 15 T is applied under vacuum and a temperature of 500°C for 5 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0076] (S.4) The flexible substrate and the large-sized spliced ​​seed crystals are bonded to the top cover of the graphite crucible. Then, 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1800°C and evacuated for 4 cycles. Argon gas is introduced to protect the thermal field. The internal pressure of the graphite crucible is controlled to 1 mbar. The graphite crucible is heated to 2000°C and the deposition is continued for 500 hours. The process is then stopped and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0077] Example 6

[0078] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0079] (S.1) As shown in the figure, a semi-insulating seed crystal with bad edges is cut by laser to form a seed crystal with a regular shape;

[0080] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 600 mm;

[0081] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a polyimide film with a surface roughness of 1 μm and a thickness of 1 mm, and a pressure of 15 T is applied under vacuum and a temperature of 500°C for 5 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyimide glue is also coated on the other side of the flexible substrate;

[0082] (S.4) The flexible substrate and the large-sized spliced ​​seed crystals are bonded to the top cover of the graphite crucible. Then, 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1000°C and evacuated for 4 cycles. Argon gas is introduced to protect the thermal field. The internal pressure of the graphite crucible is controlled to 50 mbar. The graphite crucible is heated to 2300°C and the deposition is continued for 400 hours. The process is then stopped and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0083] Comparative Example 1

[0084] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 4 Steps shown:

[0085] (S.1) Cutting a semi-insulating seed crystal with bad edges by laser to form a seed crystal with a regular shape;

[0086] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0087] (S.3) The large-sized spliced ​​seed crystal is bonded to the top cover of the graphite crucible, and then the 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1500°C, and then vacuumed and protected with argon. This process is repeated 4 times to remove air impurities. The internal pressure of the graphite crucible is then controlled to 20mbar, and the graphite crucible is heated to 2200°C for physical vapor deposition. The process is stopped after the deposition is continued for 300 hours, and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0088] Comparative Example 2

[0089] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0090] (S.1) Cutting a semi-insulating seed crystal with bad edges by laser to form a seed crystal with a regular shape;

[0091] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0092] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 5 μm and a thickness of 0.1 mm, and a pressure of 10 T is applied under vacuum and a temperature of 800°C for 10 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0093] (S.4) The flexible substrate and the large-sized spliced ​​seed crystal are bonded to the top cover of the graphite crucible, and then the 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1500°C, and then vacuumed and protected with argon. This process is repeated 4 times to remove air impurities. The internal pressure of the graphite crucible is then controlled to 20mbar, and the graphite crucible is heated to 2200°C for physical vapor deposition. The process is stopped after the deposition is continued for 300 hours, and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0094] Comparative Example 3

[0095] A method for producing colorless moissanite with high efficiency and high productivity, comprising: Figure 1 Steps shown:

[0096] (S.1) Cutting a semi-insulating seed crystal with bad edges by laser to form a seed crystal with a regular shape;

[0097] (S.2) Spin-coat a layer of polyamide glue with a viscosity of 1200 cp and a film thickness of 50 μm on the surface of the cut seed crystals using a glue spreader, and then arrange the seed crystals with the glue on the surface into a circular large-size spliced ​​seed crystal with a diameter of 800 mm;

[0098] (S.3) The side of the large-sized splicing seed crystal containing glue is bonded to a graphite paper with a surface roughness of 0.05 μm and a thickness of 0.1 mm, and a pressure of 10 T is applied under vacuum and a temperature of 800°C for 10 seconds to promote close bonding between the large-sized splicing seed crystal and the graphite paper, and then a layer of polyamide glue is also coated on the other side of the flexible substrate;

[0099] (S.4) The flexible substrate and the large-sized spliced ​​seed crystal are bonded to the top cover of the graphite crucible, and then the 5N pure silicon carbide powder source is evenly poured into the graphite crucible. The graphite crucible is heated to 1500°C, and then vacuumed and protected with argon. This process is repeated 4 times to remove air impurities. The internal pressure of the graphite crucible is then controlled to 20mbar, and the graphite crucible is heated to 2200°C for physical vapor deposition. The process is stopped after the deposition is continued for 300 hours, and the temperature is lowered until it is taken out of the furnace, thereby forming colorless moissanite.

[0100] Performance Testing:

[0101] The colorless moissanite prepared in Examples 1-6 and Comparative Examples 1-3 was observed, and then cut to remove the defective parts at the seed crystal splicing gaps, and the loss rate of the moissanite was calculated. The results are shown in Table 1 below:

[0102] Table 1

[0103] project Loss rate Appearance Example 1 15.6% Strong bonding, uniform seed arrangement, and smooth growth interface Example 2 15.1% Strong bonding, uniform seed arrangement, and smooth growth interface Example 3 15.5% Strong bonding, uniform seed arrangement, and smooth growth interface Example 4 14.8% Strong bonding, uniform seed arrangement, and smooth growth interface Example 5 18.6% Strong bonding, uniform seed arrangement, and smooth growth interface Example 6 16.9% Strong bonding, uniform seed arrangement, and smooth growth interface Comparative Example 1 26.3% Strong bonding, wide crystal gaps, and occasional cracks Comparative Example 2 18.6% Strong bonding, uneven crystal surface, some gaps widened, occasional cracks Comparative Example 3 27.2% Some seeds fell off and the seeds were arranged unevenly.

[0104] From the above test results, we can know that the method of the present invention can effectively improve the preparation efficiency of colorless moissanite. At the same time, by introducing a flexible substrate during the deposition process, the probability of adverse phenomena occurring in colorless moissanite is effectively reduced, thereby significantly reducing the loss rate of colorless moissanite.

[0105] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but this will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for producing colorless moissanite with high efficiency and high productivity, characterized in that: The following steps are involved: (S.1) cutting the semi-insulating seed crystal to obtain a seed crystal with a regular shape; (S.2) coating the surface of the seed crystals with regular shapes with glue, the glue film thickness of which is 1-100 μm, and arranging and splicing them to obtain large-sized spliced ​​seed crystals; (S.3) bonding the large-sized splicing seed crystal to the surface of the flexible substrate, and then coating the other side of the flexible substrate with glue, wherein the glue film thickness is 1-100 μm; (S.4) bonding the flexible substrate together with the large-sized splicing seed crystals into a physical vapor deposition device, and depositing silicon carbide crystals on the surface of the large-sized splicing seed crystals by physical vapor deposition, wherein the gas pressure during the physical vapor deposition process is 1-50 mbar, the temperature is controlled at 2000-2400° C., and the physical vapor deposition time is 100-500 hours, thereby forming colorless moissanite; The glue in step (S.2) and step (S.3) is any one of photoresist, paraffin, polyamide, and white sugar solution; The flexible substrate is a combination of one or more of graphite paper, polyimide film, polysiloxane film and ultra-thin glass.

2. The method for producing colorless moissanite with high efficiency and high productivity according to claim 1, characterized in that: The semi-insulating seed crystal in the step (S.1) is a high-purity semi-insulating silicon carbide wafer with poor edges.

3. A method for producing colorless moissanite with high efficiency and high productivity according to claim 1 or 2, characterized in that: The seed crystal thickness in the step (S.1) is 300-500 μm; The diameter of the large-sized spliced ​​seed crystal in the step (S.2) is 300-800 mm.

4. The method for producing colorless moissanite with high efficiency and high productivity according to claim 1, characterized in that: The glue coating method in step (S.2) and step (S.3) is spin coating by a glue spreader; The glue has a viscosity of 1000-1500cp.

5. A method for producing colorless moissanite with high efficiency and high productivity according to claim 1 or 4, characterized in that: The bonding process of the large-size spliced ​​seed crystal and the flexible substrate in the step (S.3) includes: applying a pressure of 1-15T under vacuum and a temperature of 500-1200°C.

6. The method for producing colorless moissanite with high efficiency and high productivity according to claim 1, characterized in that: The surface roughness of the flexible substrate is 0.1-2 μm, and the thickness is 0.1-1 mm.

7. The method for producing colorless moissanite with high efficiency and high productivity according to claim 1, characterized in that: The physical vapor deposition device comprises a hollow graphite container, the interior of the graphite container is filled with high-purity silicon carbide powder, and the flexible substrate is bonded to the top of the graphite container.

8. A method for producing colorless moissanite with high efficiency and high productivity according to claim 1 or 7, characterized in that: The physical vapor deposition method comprises the following steps: (1) heating and evacuating the physical vapor deposition device to remove impurity gases in the physical vapor deposition device; (2) introducing argon gas into the physical vapor deposition device for thermal field protection, and adjusting the gas pressure inside the physical vapor deposition device to 1-50 mbar; (3) The temperature inside the physical vapor deposition device is controlled at 2000-2400°C, and the physical vapor deposition time is 100-500 hours.

Citation Information

Patent Citations

  • A method for preparing colorless moissanite

    CN109911899B

  • Splicing growth method for large-size monocrystal diamond

    CN114150376A

  • Method for improving joint quality of large-size single crystal diamond through secondary epitaxy

    CN115726034A